Review and Critiqueof “Fundamentals of Finance and Budget in Education Sector” - Abdollah Ansari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
For appraisal of fundamentals of finance and budget (in education sector), the framework of inspection of liberal science texts and books council was used. The results of assessment showed that history of budget in the country, principles, and steps of budget classification and methods of income and expenditure estimate have been explained in details. In some instances, people’s right to oversee government operations as a logic behind budget approval by parliament has been emphasized. The book is readable; the quality of print is relatively suitable, and the text is clear and easy to read for the most parts. Not all chapters include introduction, summary, test, picture, practice (sample) and final conclusion, and only for one chapter, practice (sample) has been presented. Phraseology general principle has not been followed in a section of the book. There is no scientific and literary editing as well. The most important shortcoming of this book is related to its lack of coverage of vast changes (advances) in public accounting systems and public financial statistics which have been used since 2003 which per se makes the majority of book outdated and old. Moreover, many regulations, institutions and methods have changed in government budgeting systems and education sector which are not reflected in this book. The other considerable shortcoming is related to lack of attention to financing education which connects theoretical issues of education economy to practical aspects like fundamentals of finance and budget in education sector. Another problem with the book is overlooking theprocesses and methods of distribution and allocation of credits among regions as well as programs and activities in education sector. Not considering political economy of budgeting as an area that operations take place is another shortcoming. Lack of attention to macroeconomic issues like government’s role in economy, budget deficit, and related views to economic concepts can also be seen. Updating book and discussing education finance issues with distribution of public credits in education sector are also suggested.